Inca state and cult lands in the Chancay and Fortaleza valleys, north-central Peruvian coast - Barraza Lescano, Sergio (2023)
Based on an analysis of archival documents, complemented by a review of material evidence of Inca affiliation reported in the coastal valleys of Chancay and Fortaleza, in this article we will study the Inca occupation of both valleys, focusing our attention on the lands worked for the Inca State.